Problemy finansowo-ekonomicznej adaptacji słowackich i maltańskich przedsiębiorstw do funkcjonowania w strefie euro – analiza porównawcza - Pujer, Klaudia (Gospodarka w Praktyce i Teorii, 2013)
This paper addresses the problems in the functioning of Maltese and Slovak companies resulting from the accession of the two Republics to the Eurozone and the intensification of the global financial crisis. The subject of inquiry have become the factors that inhibit the possibility of achieving the objectives of the company, the reasons for the realization of the difficult situation in which they found themselves, and ways to reduce the company that situation. In discussing the issue, based on the results of surveys conducted among its companies operating in Malta and Slovakia.